2014
DOI: 10.18632/oncotarget.2294
|View full text |Cite
|
Sign up to set email alerts
|

ThemicroRNA-23b/27b/24-1cluster is a disease progression marker and tumor suppressor in prostate cancer

Abstract: Our recent study of microRNA (miRNA) expression signatures in prostate cancer (PCa) has revealed that all members of the miR-23b/27b/24-1 cluster are significantly downregulated in PCa tissues. The aim of this study was to investigate the effectiveness of these clustered miRNAs as a disease progression marker and to determine the functional significance of these clustered miRNAs in PCa. Expression of the miR-23b/27b/24-1 cluster was significantly reduced in PCa tissues. Kaplan-Meier survival curves showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(151 citation statements)
references
References 39 publications
10
137
1
3
Order By: Relevance
“…20 [39], breast cancer [40], cervical cancer [41], nasopharyngeal carcinoma [42], lung carcinoma [43], and gastric cancer [37]. In contrast with a previous study [24], we hereby show that miR-24-3p levels do not significantly differ between colorectal adenocarcinoma and non-cancerous colorectal mucosae.…”
Section: Accepted Manuscriptcontrasting
confidence: 93%
“…20 [39], breast cancer [40], cervical cancer [41], nasopharyngeal carcinoma [42], lung carcinoma [43], and gastric cancer [37]. In contrast with a previous study [24], we hereby show that miR-24-3p levels do not significantly differ between colorectal adenocarcinoma and non-cancerous colorectal mucosae.…”
Section: Accepted Manuscriptcontrasting
confidence: 93%
“…In this study, ZNF238 was targeted by over-expressed miR-20b, which was reported to be an oncogenic miRNA (Li et al, 2013). Conversely, ZNF267 was a target gene of the antineoplastic miRNAs -23a and -23b (Goto et al, 2014;Xishan et al, 2014), both of which were downregulated in our study. Given that the role of miRNAs generally lies in negatively regulating target gene expression, miR-20b might be positively correlated with leukemogenesis by directly inhibiting the expression of the tumor suppressive ZNF238 protein.…”
Section: Discussionsupporting
confidence: 45%
“…Several studies have reported that numerous miRNAs may be independent biochemical recurrence prediction markers (35)(36)(37)(38). The present study aimed to investigate the potential of miR-17-92 cluster derived from surgery at the initial visit in predicting the possibility of PCa progression or metastasis, and the results obtained demonstrated that the expression status of the miR-17-92 cluster was a good prognostic marker for time to progression to biochemical recurrence.…”
Section: Discussionmentioning
confidence: 80%